The Capital-Output Ratio in Japanese Economic Development - Ranis, G. (Review of Economic Studies, 1958)
Journal Article The Capital-Output Ratio in Japanese Economic Development Get access G. Ranis G. Ranis New York Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 26, Issue 1, October 1958, Pages 23–32, https://doi.org/10.2307/2295855 Published: 01 October 1958